Enhancing yield and profitability from pulses cultivation by technological intervention using cluster approach in Sitapur district of Uttar Pradesh - YADAV, AMBREESH SINGH (Journal of Soil and Water Conservation, 2021)
Study was under taken in Sitapur district of U.P. in central India. Total 55, 65 and 78 FLDs on pigeonpea, moongbean and lentil were conducted in cluster by Krishi Vigyan Kendra-II, Sitapur, Uttar Pradesh during 2012-13, 2013-14 and 2014-15. The critical inputs were identified in existing production technology through farmers meetings and group discussion. The findings in respect of pigeonpea, moongbean and lentil average yield trend of demonstrations were 2.24, 1.04 and 2.20 t/ha and average yield increase in demonstrations plots of pigeonpea, moongbean and lentil were 46.08, 41.42 and 15.88 per cent over the farmers’ practices yield. The yield levels were considerably lower under farmers’ practices because of considerable variation in the extent of adoption of recommended technology depending upon the amount of risk involved in terms of cost, convenience, skill and knowledge about the concerned practice. Average extension gap, technology gap and technology index of pigeonpea (0.71 t/ha, 0.76 t/ha and 25.33%), moongbean (0.30 t/ha, 0.16 t/ha and 13.22%) and lentil (0.30 t/ha, 0.30 t/ha and 12.13%) were found during 2012-13 2013-14 and 2014-15, respectively. Average net return and benefit cost ratio of demonstration plots of pigeonpea, moongbean and lentil crops were ` 52,360/ha, 4.15:1; ` 41,438/ha, 4.83:1 and ` 57,596/ha, 4.27:1 higher than the farmers’ practices ` 39,633/ha, 3.94:1; ` 29,885/ha, 4.48:1 and ` 38,895/ha, 3.88:1, respectively. The productivity was better over local practice under demonstrations. Hence, pulses production and protection technology have a broad scope for increasing the area and production of pulses at each and every level i.e., farmers, state and national level.